Babalar sozi – the core of national culture - Musayeva, N. R.; Tailakova, A. A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
In this article the location is determined in spiritual life of society a place of a 100 toms edition «Words of ancestors» of Kazakh storytelling and folklore, published in scope of the government program «Cultural heritage», facilitating a more complete illumination of people’s spiritual culture of of history and systematically holistic disclose of Kazakhs’ free spirit sources. Heroic eposes, dastans, historical, novelistic, humorous verbal stories, riddles, proverbs and sayings, myths, religious and magic texts are published in this unique project. In general al the genrees of Kazakh folklore are presented, including materials of the chinese and mongolian Kazakh diaspore. In the article philosophical sense of quatrains song «Kara olen /Words of edification» is interpreted as about life’ being, perishable nature of human life, about the collision of good and evil. «Kara olen / Words of edification» is published in the 70th tom of this great edition.